2022
DOI: 10.1002/ppul.26079
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy‐related 5 gene mRNA expression and ATG5 rs510432 polymorphism in children with bronchial asthma

Abstract: Purpose: Bronchial asthma is a common chronic respiratory disease in children with complex pathogenesis, characterized by airway hyper-responsiveness, obstruction, mucus hyperproduction, and airway remodeling. Autophagy is important for cellular physiology, and the ATG5 rs510432 has recently been implicated in several fundamental characteristics of childhood asthma pathogenesis and may play a role in the disease progression. This study aims to assess the expression of ATG5 messenger RNA (mRNA) according to rs5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…SNPs are the most common genetic variations in a single nucleotide of the DNA and are also popularly found in noncoding segments. For instance, polymorphisms in the noncoding segments of ATG5, rs510432 and rs506027, are linked to susceptibility to bronchial asthma, epilepsy, and sepsis 42–44 . Recently, some studies have found that gene mutations in the coding region also affect the occurrence of various diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs are the most common genetic variations in a single nucleotide of the DNA and are also popularly found in noncoding segments. For instance, polymorphisms in the noncoding segments of ATG5, rs510432 and rs506027, are linked to susceptibility to bronchial asthma, epilepsy, and sepsis 42–44 . Recently, some studies have found that gene mutations in the coding region also affect the occurrence of various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, polymorphisms in the noncoding segments of ATG5, rs510432 and rs506027, are linked to susceptibility to bronchial asthma, epilepsy, and sepsis. [42][43][44] Recently, some studies have found that gene mutations in the coding region also affect the occurrence of various diseases. rs2245214 and rs573775 in the coding segments of ATG5 were associated with susceptibility to chronic Q fever, non-small cell lung cancer, and systemic lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…ATG5, as one of the essential proteins regulating autophagy, is considered to overexpress and mediate immune responses in asthma [ 12 , 15 , 20 ]. Previous reports suggest that compared with HCs, ATG5 is highly expressed in asthma children [ 13 , 15 ]. However, no study has explored ATG5 level and its relationship with clinical features in adult asthma patients.…”
Section: Discussionmentioning
confidence: 99%
“…The above studies reveal the potential of ATG5 as a marker for asthma management. However, the previous studies have only shown an abnormal expression of ATG5 in asthma children [ 13 , 15 ]. Moreover, the clinical roles of ATG5 in adult asthma patients have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Autophagy has been associated with inflammatory diseases, cardiovascular diseases, neurodegenerative diseases, and cancers. [ 5 ] Ahmad et al [ 6 ] highlighted the pivotal role of ARG ATG5 in pediatric asthma. Furthermore, microRNA (miRNA, miR)-30a was identified to target ATG5, thereby inhibiting autophagy, which subsequently leads to a reduction in airway fibrosis in patients with asthma.…”
Section: Introductionmentioning
confidence: 99%